Directive Speech Acts and Teachers' Speaking Strategies in Negotiation Text Learning in Indonesian Language - Rizky Khoirunnisa Siregar; Ermawati Arief; Ena Noveria; Herlin Triana (Raja Zulkarnain Education Foundation, 2026)
Teacher-student interactions in negotiation text learning utilize language as the primary means of classroom management. This study aims to describe the forms of directive speech acts and politeness strategies used by teachers in Indonesian language learning in class X at SMK Negeri 3 Padang. This is a qualitative study using descriptive methods, aiming to deeply uncover the meaning and phenomena of speech in a natural, uncontrived context. The research data consisted of teacher utterances containing directive speech acts, such as commands, requests, prohibitions, invitations, and advice. These were obtained through non-participatory observation, audio-video recordings from the opening to the closing of the lesson, semi-structured interviews, and documentation. The data sources were the Indonesian language teachers of class X who were observed in several meetings. The researcher acted as the primary instrument, supported by recording devices and observation sheets. Data validity was ensured through data and source triangulation, member checking, and diligent observation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions repeatedly until credible findings were obtained. The results of the study show that the most dominant form of directive speech act is an order; direct strategies are used in situations that require assertiveness and efficiency, while indirect strategies are used to maintain politeness and create a conducive learning atmosphere, thus supporting the effectiveness of interactions and achieving the learning objectives of negotiation texts.